Length-Weight Relationship of Two Puffer Fishes, Lagocephalus sceleratus and Lagocephalus spadiceus, From Iskenderun Bay, Northeastern Mediterranean, Turkey - Basusta, Asiye; Basusta, Nuri; Ozer, Ebru Ifakat (Zoological Soc Pakistan, 2013)
In recent years, a noticeable increase in the population of puffer fish in the Northeastern Mediterranean has been reported by the fishermen in the region. But there are no any studies on these fishes in term of fisheries management. This study is to determine the length-weight relationships of Lagocephalus sceleratus and Lagocephalus spadiceus captured by commercial bottom trawlers using trawl nets at 24 and 50meter depths and gill nets at depths approximately 8 to 20 meters in the northeastern Mediterranean Sea. The exponent b values were 2.6733 for male and 2.7183 for female of L. spadiceus, and 2.6446 for male and 2.915 for female of L. sceleratus. The types of growth for both sexes was negative allometric growth for L. spadiceus , but an indicated isometric growth for females and negative allometric growth for males of L. sceleratus. This study also provides a maximum total length of 37.4 cm for L. spadiceus.
Keywords: Lagocephalus sceleratus; Lagocephalus spadiceus; Length-weight relationships; pufferfish; Eastern Mediterranean